Drainage anomalies as indicators of soft-linked deformation zones between neotectonic structural highs in the Precordillera, Central Andes of Argentina - Terrizzano, Carla Marina (2014)
Between 31°45'-32°15' S, the western piedmont of the Ansilta block in the Precordillera of Argentina has been uplifted in Quaternary times through folds, blind faults and faulted blocks that form discrete and evident areas of neotectonic deformation (structural highs). In between, subtle tectonic perturbations of the fluvial landforms (drainage anomalies), such as diverted and entrenched streams, asymmetric basins, incision anomalies, convex-upward longitudinal stream profiles, dammed rivers and broom-shaped patterns allow the recognition of areas of incipient deformation. We combined the analyses of both the structural highs and the drainage anomalies areas to investigate the role of the latest as an expression of soft-linkage areas in fault systems. The structural highs would be interpreted as isolated features without the consideration of the drainage anomalies areas between them. Moreover, linking the structural highs using the drainage anomalies reveals the extent of major Quaternary deformation belts in their initial development stages.